Troubleshooting iOS : solving iPhone and iPad problems - McFedries, Paul (Apress, 2017)
This book is a comprehensive guide to understanding and solving many different kinds of iPhone and iPad problems. Both general troubleshooting techniques applicable in a wide variety of situations as well as specific fixes for topics such as networking, apps, photos, the battery, and syncing are covered. Glitches, hiccups, and crashes just aren't supposed to happen with iOS, but alas, all too often they do. It is these non-obvious fixes, workarounds, and preventative measures that form the core of iOS Troubleshooting. With clear, straightforward prose, this book will take the reader through hundreds of iOS problems, explain the reasons for them, and provide easy to understand solutions to get the device (and you) back in business.